Virginity and the clutch size behavior of a parasitoid wasp where mothers mate their sons - Abe, Jun; Innocent, Tabitha M.; Reece, Sarah E.; West, Stuart A. (Behavioral ecology, 2010)
Theoretical and empirical research on the evolution of clutch size has proved to be an extremely productive area of evolutionary biology. A general prediction is that individuals should produce a smaller number of offspring when resources are more limited, such as when multiple individuals compete for the same resources for their development. However, we expect that the opposite prediction arises with virgin females of haplodiploid species, which are subject to extreme local mate competition. We test the key assumption and predictions of this theory with the parasitoid wasp Melittobia australica. Our data demonstrate that there is a trade-off between the size of the first and subsequent clutches and that virgin females adjust their production of sons according to the mating status (mated or not) of cofounding females. We also found that mated females facultatively change their offspring sex ratio in response to the mating status of cofoundresses. We discuss the potential mechanisms used to recognize the mating status and the implications of our results in the context of the extremely female-biased sex ratios observed across Melittobia species.